ENDEMISME SPESIES BIOTA PERAIRAN: STUDI KASUS PADA IKAN CAPUNGAN BANGGAI (Pterapogon kauderni) - Ucu Yanu Arbi (Pusat Penelitian Oseanografi LIPI, 2022)
A species becomes endemic if found only in one place and not found elsewhere. Physical, climatic, and biological factors can cause endemism through two commonly known mechanisms, namely